Development of Student Worksheets Based on Problem Based Learning on Excretory System Material for Grade XI Senior High School - Lubis, Rizka Riswani; Tanjung, Indayana Febriani; Adlini, Miza Nina (Bioeduca : Journal of Biology Education, 2023)
The Problem Based Learning (PBL) model of high-level intellectual learning, namely analysis, criticism, and conclusions is applied to LKPD used as a support in learning activities according to the competencies achieved. The research aims to determine the validity, practicality, and effectiveness of PBL-based worksheets on excretory system material. This type of research is Research and Development (RnD) with a 4D model (Define, Design, Development, Disseminate). The results showed that student worksheets based on problem-based learning were made with a score of 100% (content validation) very valid criteria, 75% (construct validation) valid criteria, 98% (biology teacher response), and 81.5% (student responses) very practical criteria. The LKPD proved to be effective in achieving increased results (N-Gain) by achieving a high-class average score of 0.702. And it was concluded that the PBL-based LKPD that was made was valid, practical, and effectively applied in classroom learning activities